1969
DOI: 10.1203/00006450-196907000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Glyoxylate in Nonketotic Hyperglycinemia

Abstract: Hyperglycinemia is an error of amino acid metabolism in which there are increased amounts of glycine and normal amounts of other amino acids in blood, urine, and cerebrospinal fluid. There are a t least two different types of hyperglycinernia. We recently reported on the metabolism of glycine in nonketotic hyperglycinernia [I]. A defect was found in the formation of14C02 from glycine-1-14C and in the conversion of the carbon 2 of glycine to the carbon 3 of serine. These findings were consistent with a defect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1970
1970
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…I~ patients survive the early months, mental retardation, decerebrate rigidity and hypertonus are observed in the later phases o~ their lives. Tracer stUdies in some o~ these patients show a normal glycine oxidation (Gerritsen et al, 1969) and a block in the glycine cleavage system in both the brain and the liver (Perry et al, 1975a;Tada et al, 1974;Trijbels et al,1974). An increiSe-rn glycine levelS-or-cerebrospinal ~lui~ and blood is also observed (Scriver et al, 1975;Perry et al, 1975b) • The CSF to blood p,lycine ratio -rs higher than in-cOntrol sub,jects, which ~its the criterion used by some physicians to classify a disease as a genetic glycinemia, as opposed to other syndromes which indirectly result in high blood glycine levels (Applegarth and Poon, 1975).…”
Section: Clinical Aspects Of Glycinementioning
confidence: 96%
“…I~ patients survive the early months, mental retardation, decerebrate rigidity and hypertonus are observed in the later phases o~ their lives. Tracer stUdies in some o~ these patients show a normal glycine oxidation (Gerritsen et al, 1969) and a block in the glycine cleavage system in both the brain and the liver (Perry et al, 1975a;Tada et al, 1974;Trijbels et al,1974). An increiSe-rn glycine levelS-or-cerebrospinal ~lui~ and blood is also observed (Scriver et al, 1975;Perry et al, 1975b) • The CSF to blood p,lycine ratio -rs higher than in-cOntrol sub,jects, which ~its the criterion used by some physicians to classify a disease as a genetic glycinemia, as opposed to other syndromes which indirectly result in high blood glycine levels (Applegarth and Poon, 1975).…”
Section: Clinical Aspects Of Glycinementioning
confidence: 96%
“…The reverse reaction with glycine and pyruvate is barely detectable in crude liver homogenates (Rowsell et al, 1969b), and not at all with L-alanineglyoxylate aminotransferase purified from human liver (Thompson & Richardson, 1967). It seems likely therefore that the enzyme does operate to convert glyoxylate into glycine, a process that undoubtedly can occur in vivo in the rat (Weinhouse & Friedman, 1951;Weissbach & Sprinson, 1953) and in man (Gerritsen et al, 1969).…”
mentioning
confidence: 99%
“…Gerritsen et al [14] supposed originally that nonketotic hyperglycinemia was associated with a defect i n the glycine oxidase system; however, later such a defect was ruled out [15]. Thereafter, Ando et al [3] demonstrated a defect in viuo in the formation of l4CO2 from (I-l4C)glycine and a complete deficiency in the conversion of (2-1")glycine to (3-14C)serine.…”
Section: Discussionmentioning
confidence: 99%